Reaction of simple sterile sugar beet hybrids to regulated environmental factors for sugar yield - М. О. Корнєєва; М. М. Ненька (Plant Varieties Studying and Protection)
Sugar yield, an important indicator, is resulting from interaction of two components: the yield and sugar content, both they are controlled by polygenes, and influenced significantly by environment. A.V. Kilchevskyi and L.V. Hotyliova pointed to the fact that in breeding, contrary to evolution, stabilizing forms are dominated by driving ones, which determine the growth response to regulated factors and decreased resistance to non-regulated environmental factors [1]. A relevant breeding trend is to create the genotypes adequate with certain technologies, so to say «low input variety high input variety» i.e. varieties with low and high energy contribution to technology. From this perspective, selection of stable in their manifestation lines against the analyzing backgrounds has become an important element of the breeding process [2]. Home scientists, such as A.L. Mazmulov and M.S. Hrytsyk have contributed greatly to the development and application of the agro-backgrounds [3, 4].